Kandungan Logam Berat pada Kerang Kepah (Meritrix meritrix) dan Air Laut di Perairan Banjarmasin - Jovita Tri Murtini; Rosmawaty Peranginangin (Jurnal Perikanan Universitas Gadjah Mada, 2006)
Studies on heavy metal content of Meritrix meritrix and surrounding waters as well as the quality of Banjarmasin waters were done. Observation was carried out in June, August and October 2003 at 6 sampling points, 3 stations were 1 mile while 3 others were 2 miles from coastal line. Distance between stations was approximately 1 mile. The samples collected from each station were hard clam (Meritrix meritrix), sea water and sediment. Heavy metals content, Hg, As, Cd, Cu and Pb, in hard clam and mercury content in sea water and sediment were analyzed by atomic absorption spectrophotometer (AAS). The result showed that Hg content of Banjarmasin waters in June, August and October 2003 were 6.05, 3.17, and 4.91 ppb, respectively, indicated that Banjarmasin waters had been polluted by mercury. Whereas the hard clam in Banjarmasin waters contained Hg (1.91 ppb), As (0.88 ppb), Cd (0.22 ppb), Cu (0.46 ppb), and Pb (0.32 ppb) which were still under the maximum concentration for consumable clam.